2012
DOI: 10.2519/jospt.2012.3803
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Patellofemoral Pain Syndrome: A Systematic Review

Abstract: Patellofemoral pain syndrome (PFPS) is the most frequently diagnosed condition in patients younger than 50 years with knee complaints. While the general practitioner sees an average of 5 or 6 new patients with PFPS per year , the incidence of PFPS in the general population is still unknown. 4,37 Women have a higher incidence of PFPS than men, 33 and incidence rates of 25% to 43% have been reported in sports medicine and during basic military T T STUDY DESIGN: Systematic review. T T OBJECTIVES:To systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
147
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 41 publications
7
147
0
5
Order By: Relevance
“…An example is vastus medialis, where substantial alterations in fibre alignment are seen between proximal and distal muscle portions (Smith et al , 2009). The distal oblique fibres are thought to play a pivotal role in the kinematics and alignment at the patellofemoral joint (Berry et al , 2008, Fagan and Delahunt, 2008, Lin et al , 2008 and physiological or biomechanical dysfunction of this muscle are reported to contribute to patellofemoral pain (PFP) (Lankhorst et al , 2012). Recent research has used RUSI to assess the pennation angle of these oblique muscle fibres in cadaveric specimens (Engelina et al , 2012) and assess muscle volume in individuals with PFP (Lin, Lin, 2008, Jan et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…An example is vastus medialis, where substantial alterations in fibre alignment are seen between proximal and distal muscle portions (Smith et al , 2009). The distal oblique fibres are thought to play a pivotal role in the kinematics and alignment at the patellofemoral joint (Berry et al , 2008, Fagan and Delahunt, 2008, Lin et al , 2008 and physiological or biomechanical dysfunction of this muscle are reported to contribute to patellofemoral pain (PFP) (Lankhorst et al , 2012). Recent research has used RUSI to assess the pennation angle of these oblique muscle fibres in cadaveric specimens (Engelina et al , 2012) and assess muscle volume in individuals with PFP (Lin, Lin, 2008, Jan et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…No level of evidence was reported for the four reviews which were not systematic or meta-analysis. The results showed two clinical test reviews of high quality systematic reviews of case control or cohort studies [34,35], one high quality meta-analysis of RCT's [36] and three high quality systematic reviews of case control or cohort studies on risk factors [9,17,37], three high quality meta-analyses or systematic reviews of RCT's [11,38,39] and three high quality systematic reviews of case control or cohort studies on exercise treatment [12,13,40] and two high quality systematic reviews of case control or cohort studies on outcome measures [41,42].…”
Section: Critical Appraisalmentioning
confidence: 99%
“…The reason was that this study reported to have a priori design (AMSTAR question-1, PRISMA checklist item-5). On the opposite side, the two studies from Lankhorst et al [9,36] were the only studies which assessed the likelihood of publication bias (AMSTAR Question-10, PRISMA checklist item-15). All studies performed a comprehensive literature search (question 3 AMSTAR) which was anticipated because this criterion was one of the inclusion criteria for the current review.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…This imbalance is considered the main factor for the appearance of the symptoms, which changes the patellar kinematics and contributes to the increase of the patellofemoral reaction and The decreased strength of the quadriceps, the main dynamic stabilizer of the patella in the femoral trochlea, is directly related to the incidence of patellar-femoral pain and plays an important role in the onset of PFPS. Therefore, it is pointed out as a risk factor, which was also concluded in a recent systematic review 6 . For patients diagnosed with PFPS, conservative treatment is always considered as the first and best option.…”
Section: Introductionmentioning
confidence: 99%